2014
DOI: 10.3389/fpsyg.2014.01289
|View full text |Cite
|
Sign up to set email alerts
|

Magic and memory: using conjuring to explore the effects of suggestion, social influence, and paranormal belief on eyewitness testimony for an ostensibly paranormal event

Abstract: This study uses conjuring to investigate the effects of suggestion, social influence, and paranormal belief upon the accuracy of eyewitness testimony for an ostensibly paranormal event. Participants watched a video of an alleged psychic seemingly bending a metal key by the power of psychokinesis. Half the participants heard the fake psychic suggest that the key continued to bend after it had been put down on a table and half did not. Additionally, participants were exposed to either a negative social influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For example, it could generate false memories in the spectators’ minds (e.g., Loftus, 1997; Loftus, 1992; see also Lamont & Wiseman, 2001, for the Indian rope illusion). Wilson and French (2014) replicated Wiseman and Greening's (2005) experiment with an accomplice witness. Results showed that after watching video, when the accomplice witness suggested that the key was still bending, more participants reported that the key continued to bend on the table compared with a condition without witness or a condition with a negative suggestion (i.e., “the key did not continue to bend”).…”
Section: Other Psychological Devices In the Service Of Magiciansmentioning
confidence: 99%
“…For example, it could generate false memories in the spectators’ minds (e.g., Loftus, 1997; Loftus, 1992; see also Lamont & Wiseman, 2001, for the Indian rope illusion). Wilson and French (2014) replicated Wiseman and Greening's (2005) experiment with an accomplice witness. Results showed that after watching video, when the accomplice witness suggested that the key was still bending, more participants reported that the key continued to bend on the table compared with a condition without witness or a condition with a negative suggestion (i.e., “the key did not continue to bend”).…”
Section: Other Psychological Devices In the Service Of Magiciansmentioning
confidence: 99%
“…One week after having watched a video of a car accident, participants were explicitly asked: “Did you see any broken glass?” The reported false memories of broken glass could not have been derived directly from the video, because the video did not actually show any broken glass; thus, the false memory was arguably induced by the question itself. Other researchers have demonstrated that false verbal suggestions presented co-currently with events can also induce false reports ( Wiseman et al, 2003 ; Wiseman and Greening, 2005 ; Wilson and French, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…We wonder if these magic memories are similar to those acquired in especially emotional circumstances (flashbulb memories), in which the vivid memory of the experience does not guarantee the trustworthiness of its details (Hirst et al, 2015). Along these lines, memorability studies on supposedly paranormal experiences (some published more than 130 years ago) show that memories are very unreliable, and that, depending on the circumstances, there is a propensity to remember events that have not happened (Hodgson & Davy, 1887;Besterman, 1932;Wiseman & Morris, 1995;Wilson & French, 2014). Subjects are also susceptible to manipulation through suggestion and instructions (Wiseman, Greening & Smith, 2003;Wiseman & Greening, 2005;Wilson & French, 2014).…”
Section: Episodic Memoriesmentioning
confidence: 99%
“…Along these lines, memorability studies on supposedly paranormal experiences (some published more than 130 years ago) show that memories are very unreliable, and that, depending on the circumstances, there is a propensity to remember events that have not happened (Hodgson & Davy, 1887;Besterman, 1932;Wiseman & Morris, 1995;Wilson & French, 2014). Subjects are also susceptible to manipulation through suggestion and instructions (Wiseman, Greening & Smith, 2003;Wiseman & Greening, 2005;Wilson & French, 2014). We believe that these studies can be a good reference to plan the necessary and yet non-existent studies on the subsequent memorability of magic shows.…”
Section: Episodic Memoriesmentioning
confidence: 99%